Comparison of Uncontrolled and Device-Induced Therapeutic Hypothermia in Newborn Infants with Hypoxic Ischemic Encephalopathy - A. A. Zarubin (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. Newborn infants who have undergone severe birth asphyxia have a high risk of neurological disorders and death. The most effective method for the treatment of hypoxic ischemic encephalopathy caused by intrapartum asphyxia is therapeutic hypothermia, or targeted temperature management. Currently, there are no large studies comparing its different methods, therefore the aim of our study was to compare the effectiveness of device-induced and uncontrolled therapeutic hypothermia in newborn infants who underwent intrapartum asphyxia.Materials and methods. Study design: we conducted a retrospective, longitudinal, cohort study in 39 newborn infants born in severe asphyxia and receiving uncontrolled therapeutic hypothermia (group 1), and in 48 newborn infants born in severe asphyxia and receiving device-induced therapeutic hypothermia (group 2). Statistical data processing was carried out using standard techniques.Results. The body temperature in newborn infants of both groups was reduced to 33.5 °C within the first hour, but when using uncontrolled therapeutic hypothermia, the body temperature fluctuated from 32 to 35 °C. Device-induced therapeutic hypothermia has a more effective neuroprotective effect as compared to uncontrolled hypothermia (p< 0.05) and more rapidly stabilizes metabolism in newborns due to a decrease in lactate levels (p < 0.05). In newborns device-induced therapeutic hypothermia stabilizes hemodynamics more quickly compared to uncontrolled therapeutic hypothermia (p < 0.05). Device-induced therapeutic hypothermia reduces the period of hospitalization in the neonatal intensive care unit (p < 0.05), the risk of cerebral edema (p < 0.05) and of the repeated episodes of seizures (p < 0.05). Conclusion. Using uncontrolled therapeutic hypothermia causes a high risk of unintentional fluctuations in rectal temperature towards both hypothermia and rewarming, which can aggravate the severe condition of newborn infants. Device-induced therapeutic hypothermia has a more effective neuroprotective effect.